Revealing changes in the technical parameters of the teat cup liners of milking machines during testing and production conditions - Paliy, Andriy; Палій, Андрій Павлович; Aliiev, Elchyn; Алієв, Ельчин Бахтияр огли; Paliy, Anatoliy; Палій, Анатолій Павлович; Ishchenko, Katerina; Іщенко, Катерина; Lukyanov, Igor; Лук’янов, Ігор; Dobrovolsky, Volodymyr; Добровольський, Володимир; et al. (Scientific Route OÜ, Estonia, 2021)
To implement effective cow milking, it is necessary to take into account the peculiarities of the milk flow process, the milking machine's adaptability to perform the given technological functions. The aim of research is to establish changes in the design and technological parameters and physical and mechanical properties of teat cup liner of milking machines during its testing and in production conditions. The results obtained will make it possible to make a rational choice of rubber, ensure an efficient milking process during its service life. It is found that the tensile strength of silicone teat cup liner at the beginning of operation was 1.6 times higher than that of a rubber compound, and after 6 months. operation – 1.7 times. With respect to the relative elongation, this difference was 1.4 times, and after operating time – 1.3 times. Studies have proven that rubber during operation changes its physical and mechanical properties: the length of the active part increased by 3.1 mm; wall thickness – 0.2 mm. It is found that the most intensively elastic properties of teat cup liner changed during the first 10–20 days. After 10 days, the closing vacuum increased by 16.6 % compared to the initial one, and after 20 days by 23.3 %, which amounted to 8.57 and 9.06 kPa, respectively. Up to 420 hours of operation, the clamping vacuum reached 11.3 kPa, which is 5.8 % lower than the requirements for toughening teat cup liner for rejection. In general, over the period of experiments, the average value of the vacuum of closing the opposite walls of teat cup liner increased from 7.35 to 12.43 kPa, which is 3.6 % higher than the norm (12 kPa). As a result of experimental studies, the regularity of the rubber tension force depending on the operating time in the form of a fourth degree polynomial is obtained. It is found that after 150 hours of operation, the tensile force of teat cup liner decreased by 21 %. Для ефективного доїння корів необхідно враховувати особливості процесу протікання молока, пристосованість доїльного апарату до виконання заданих технологічних функцій. Метою дослідження є встановлення змін конструктивно-технологічних параметрів та фізико-механічних властивостей доїльного стаканчика доїльних апаратів під час його випробування та в умовах виробництва. Отримані результати дозволять зробити раціональний вибір гуми, забезпечити ефективний процес доїння протягом терміну її служби. Встановлено, що міцність на розрив силіконової підкладки для соскових чашок на початку експлуатації була в 1,6 рази вище, ніж у гумової суміші, а через 6 місяців. операція – в 1,7 рази. За відносним подовженням ця різниця склала 1,4 рази, а після напрацювання – 1,3 раза. Дослідженнями доведено, що гума в процесі експлуатації змінює свої фізико-механічні властивості: довжина активної частини збільшується на 3,1 мм; товщина стінки – 0,2 мм. Встановлено, що найбільш інтенсивно еластичні властивості вкладиша для соскових чашок змінюються протягом перших 10–20 днів. Через 10 діб вакуум закриття зріс на 16,6 % порівняно з початковим, а через 20 днів на 23,3 %, що склало 8,57 та 9,06 кПа відповідно. До 420 годин роботи вакуум затиску досяг 11,3 кПа, що на 5,8 % нижче, ніж вимоги до зміцнення вкладиша соскової чашки для відбракування. Загалом за період дослідів середнє значення вакууму замикання протилежних стінок вкладиша соскової чашки зросло з 7,35 до 12,43 кПа, що на 3,6 % вище норми (12 кПа). В результаті експериментальних досліджень отримано закономірність сили натягу гуми в залежності від часу роботи у вигляді полінома четвертого ступеня. Встановлено, що після 150 годин роботи сила розтягування вкладиша соскової чашки зменшилася на 21 %.
Виявлення змін технічних параметрів дійкової гуми доїльних апаратів під час випробувань та умов виробництва
Keywords: teat cup liner; дійкова гума; rubber parameters; параметри гуми; operating time; час роботи; service life; термін служби; tensile force; зусилля